Chromosomal introgressions from Oryza meridionalis into domesticated rice Oryza sativa result in iron tolerance - Wairich, Andriele; de Oliveira, Ben Hur Neves; Wu, Lin-Bo; Murugaiyan, Varunseelan; Margis-Pinheiro, Marcia; Fett, Janette Palma; Ricachenevsky, Felipe Klein; Frei, Michael (Oxford University Press, 2021)
Iron (Fe) toxicity is one of the most common mineral disorders affecting rice (Oryza sativa) production in flooded lowland fields. Oryza meridionalis is indigenous to northern Australia and grows in regions with Fe-rich soils, making it a candidate for use in adaptive breeding. With the aim of understanding tolerance mechanisms in rice, we screened a population of interspecific introgression lines from a cross between O. sativa and O. meridionalis for the identification of quantitative trait loci (QTLs) contributing to Fe-toxicity tolerance. Six putative QTLs were identified. A line carrying one introgression from O. meridionalis on chromosome 9 associated with one QTL was highly tolerant despite very high shoot Fe concentrations. Physiological, biochemical, ionomic, and transcriptomic analyses showed that the tolerance of the introgression lines could partly be explained by higher relative Fe retention in the leaf sheath and culm. We constructed the interspecific hybrid genome in silico for transcriptomic analysis and identified differentially regulated introgressed genes from O. meridionalis that could be involved in shoot-based Fe tolerance, such as metallothioneins, glutathione S-transferases, and transporters from the ABC and MFS families. This work demonstrates that introgressions of O. meridionalis into the O. sativa genome can confer increased tolerance to excess Fe.